Kontekst medialny fotografii mortualnej na przykładzie zdjęć pośmiertnych Stanisława Wyspiańskiego i Adama Mickiewicza - Łarionow, Dominika (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The article shows on the example of the history of the cultural presence of dead bodies of two national poets: Stanisław Wyspiański and Adam Mickiewicz – the story of the development of the press debate around death. In Wyspiański’s case: the departure of the poet, the funeral became a stand-alone media event in Cracow. Mentioned in this context, Miciewicz became the first Polish national bard, who photographed a corpse entered the general circulation. The author shows that in the modern world the presence of death in the media is limited to press releases. Current culture has marginalized death. The text provokes the question whether such a way is right?